PERBANDINGAN METODE MASTERY DENGAN KSPOSITORY LEARNING TERHADAP MOTIVASI BELAJAR PASAR MODAL SMAN1 SIBABANGUN - Ahmad Fadlan (Jurnal Akuntansi Bisnis dan Publik, 2020)
The formulation of the problem in this study is "Is there a Comparison of the methods of mastery learning with expository learning of learning motivation in the field of study of economic subject matter in the capital market of SMA Negeri 1 Sibabangun?" While the purpose of this study was to determine the increase in students' learning motivation by using the method of mastery learning with expository learning in the field of Economics subject matter in the capital market of SMA Negeri 1 Sibabangun. The type of research the author uses in this study is explanatory research (level of exploration). The author collects data by distributing questionnaires as primary data and secondary data as supporting data, then to see whether there is a comparison of mastery learning methods with expository learning of learning motivation in the field of study of economic subject matter in capital market capital students in SMA Negeri 1 Sibabangun, the authors use polled variance t-test formula. From the test score data using the mastery learning method, the highest score obtained by students is 95 and the lowest is 70 while the average is 61.52 and the standard deviation is 5.19. Then from the data of learning motivation test values using the method of expository learning obtained the highest value of students 90 and the lowest 70 while the average of 52.24 and a standard deviation of 7.89 then the alternative hypothesis Ha can be accepted.